Model Manajemen Risiko Infrastruktur Transportasi Terhadap Dampak Perubahan Iklim Dan Banjir - Artosin (CV. SINAR HOWUHOWU, 2026)
Global climate change has significantly affected the sustainability of transportation infrastructure, particularly due to the increasing intensity and frequency of floods in various regions. Roads, bridges, and other transport networks have become more vulnerable to physical damage and operational disruptions. This study aims to develop an adaptive risk management model to address the impacts of climate change and flooding on transportation infrastructure. The approach employs ISO 31000:2018-based risk analysis supported by spatial data, hydrological modeling, and the integration of disaster mitigation policies. The results indicate that the implementation of a technology-based and adaptive governance risk management model can enhance transportation infrastructure resilience against extreme climate risks. Furthermore, the study highlights the importance of cross-sector collaboration among government, academia, and practitioners in applying sustainable adaptation and mitigation strategies.